STOCK ASSESSMENT AND BIOLOGY OF JOHNIUS GLAUCUS (DAY) OFF THE NORTHWEST COAST OF INDIA - DEVARAJ, M.; KAMAT, S. S. (Journal of Indian Fisheries Association, 2015)
The stock size and biology of Johnius glaucus (Day) resource off the northwest coast of India were studied for 1982-83 and 1983-84. The total length at the end of 6, 12, 18, 24 and 26 months was 121 mm, 183 mm, 237 mm, 261 mm and 264 mm respectively. The length growth parameters were : Loo = 300 mm, K ::::: 0.0807 (monthly) and t 0 = -0.51 month. The weight growth parameters were : Woo = 317g, K = 0.0762 (monthly) and t 0 = -0.41 month. The exploited stock mainly composed of 1/2 +and 1+ age groups. The annual Z, M and F were 2.34, 1.49 and 0.85 respectively. The lb, tb, lr, tr and selection factor K were 155 mm, 0.75 year, 65 mm, 0.25 year and 3.875 respectively. The Yw/R was optimum at the exploitation rate (E) of 0. 75 and codend mesh size of 37 mm. The total stock for 1982-83 and 1983-84 was 14,624 and 26,190 tons respectively. The standing stock of 1982-83 -and 1983-84 was 5,645 and 10,110 tons respectively. The MSY for 1982-83 and 1983-84 was 6,623 and 11,788 tons respectively. The F and Z was lowest in 0+ age group and highest in 1+ age group.